(untitled) (Revista Innova Educación, 2022)
The aim of this work is to identify through a systematic review of different innovative educational practices in Higher Education. For this, a search of scientific articles was carried out in different Scopus and Web of Science databases, where a total of 1470 documents were acquired, which, after applying the inclusion criteria, left 20 works for review. The results show that creative practices favor the construction of the teaching-learning process and the development of skills. The teacher must take into account the contextualization of knowledge and start from the center of interest of the students, to promote attitudes in new procedures based on innovation, promoting skills that predispose the student towards motivation and involvement. In conclusion, it is suggested that new studies will take into account the results found in this study. This could encourage the acquisition of knowledge based on cooperation and motivation, divergent thinking and the inclusion of students.